Photodynamic therapy for actinic keratosis in organ transplant patients. (10th December 2011) - Basset‐Seguin, N.; Baumann Conzett, K.; Gerritsen, M.J.P.; Gonzalez, H.; Haedersdal, M.; Hofbauer, G.F.L.; Aguado, L.; Kerob, D.; Lear, J.T.; Piaserico, S.; Ulrich, C.
Abstract Background The incidence of actinic keratoses (AK) and non‐melanoma skin cancer (NMSC) in organ transplant recipients (OTRs) is significantly higher than in immunocompetent patients. Rates of progression and recurrence following treatment are higher too, in part due to the effects of the immunosuppressant drugs. Conventional therapies for AK, using curettage, cryotherapy, surgical excision, topical therapies and photodynamic therapy (PDT), are often less effective, and may be inappropriate, for treating the greater numbers and extent of lesions in OTRs. Moreover, there are no specific protocols for treating this patient population that take into account the need for more frequent treatment and the increased pain associated with treating larger areas. Objectives Recently, a pan‐European group of dermatologists with expertise in this area met to share current best practice in PDT for the treatment of AK in OTRs. Methods The group identified areas where PDT currently is not meeting the needs of these patients and discussed how these gaps might be addressed. Results/Conclusions This position article summarizes those discussions and makes recommendations concerning a standardized protocol for treating OTRs, for a large randomized controlled trial to provide robust data on safety, efficacy and optimal pain control, and to provide pharmaco‐economics data that can be used to support extended reimbursement in this patient group. The authors also recommend a second clinical trial to further investigate induced immunosuppression with PDT in healthy volunteers.